(untitled) (Bangladesh Journal of Medical Science, 2014)
ADPKD presenting as congestive cardiac failure due to dilated cardiomyopathy is rare. ADPKD is an inherited systemic disorder with major renal manifestation and in some cases extrarenal manifestation or combination of both. In this report 45 year male patient presented with complains of dyspnoea, abdominal distension, pain right hypochondriac region. He was hospitalized, examined clinically and advised various bio-chemical and imaging tests. The finding was suggestive of ADPKD with dilated cardiomyopathy with congestive cardiac failure. He was managed with diuretics, ACE inhibitors, digoxin, Moist oxygen inhalation and he responded to the treatment. DOI: http://dx.doi.org/10.3329/bjms.v14i1.16635 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.85-86